Defending Truthmaker Non‐Maximalism. (5th December 2014) - Simpson, Matthew
Abstract Jago (2012) argues that truthmaker non‐maximalism, the view that some but not all truths require truthmakers, is vulnerable to a challenge from truths which ascribe knowledge of propositions about things which don't exist. Such truths, Jago argues, can only be dealt with using maximalist resources. I argue that Jago's point relies on the claim that the relevant truths require truthmakers, a point that non‐maximalists can coherently and plausibly deny. Moreover, I argue that by making use of a safety account of knowledge, non‐maximalists can fully answer Jago's challenge.